Assessment of quantitative factors of variability of parameters of stockwork deposits - A. A. Makarcheva; O. I. Guskov (Известия высших учебных заведений: Геология и разведка, 2016)
On the basis of specification areas, created in three stockwork deposites - Pervomauskaya, Sherlovaya Gora and Krutoy of Pyrkayiskiy tin ore unit, differing from each other in internal structure, the type of variation of useful components’ contents was analyzed. At stockwork deposits with steep ore-bearing veins’ dip angles the low representativeness of the results of testing on the specification areas was explored, created by vertical drilling of blasting holes. The results of the research showed that the possibility of selective mining should be estimated on the basis of a detailed study of the structural features of ore-bearing veins, which affect the type of variation of the useful components’ contents.